Towards a life after retail? The relationship between human capital and career outcomes in retail - Helena Nilsson; Mikaela Backman; Özge Öner (Institute of Retail Economics (HFI), 2020)
The retail sector accounts for a large share of employment in many economies, and many young individuals regard the retail sector as a steppingstone in the labor market. As the retail sector comprises various types of employment and diverse tasks, those employed in the retail sector are able to transition across different roles. Retail firms, however, often experience high labor turnover, which is costly to firms. This paper addresses how the human capital of full-time retail employees relates to labor turnover. We study individuals working in the retail sector between 1990 and 2018 and analyze how their human capital is associated with their likelihood of remaining in the same establishment and/or in the retail sector at large. Results indicate that firm-specific human capital decreases the probability of quitting, while formal education has the opposite effect. Industry experience and specific retail education, however, decreases the probability of leaving an establishment.
Keywords: J24; J62; L81; 330; retail; human capital; experience; education; career outcomes; Sweden